The Halls Creek Way of Residential Child Care: Protecting Children is Everyone's Business - Hodgkins, Kylie; Crawford, Frances; Budiselik, William (Australian Academic Press, 2013)
This paper describes the collaboration between an Aboriginal community and Western Australia's (WA) Department for Child Protection (DCP) in designing and operating a residential child care facility in a predominantly Aboriginal community. Research literature has established that the effective operation of child protection systems in remote Aboriginal communities requires practitioners and policy-makers to have awareness of local and extra-local cultural, historical and contemporary social factors in nurturing children. This ethnographic case study describes how a newspaper campaign heightened public and professional awareness of child abuse in the town of Halls Creek, in WA's Kimberley region. With its largely Aboriginal population, Halls Creek lacked the infrastructure to accommodate an inflow of regional people. Homelessness, neglect and poverty were widespread. Within a broader government and local response, DCP joined with community leaders to plan out of home care for children. Detailed are the importance and complexities of negotiating between universal standardised models of care and local input. Strategies for building positive relationships with children's family while strengthening both parenting capacity and community acceptance, and use of the facility are identified. Key to success was the development of a collaborative ‘third-space’ for threading together local and professional child protection knowledge.